The Comparison between Black Cumin Extract and Betel Leaf Extract As Antifungal Potential to Candida Albicans on Acrylic Resin Denture Base - Hastoro Pintadi; Urai Rifaldy Aryandi (Universitas Muhammadiyah Yogyakarta, 2022)
Porosity in acrylic resin denture base causes a rough surface and can absorb fluid, leading to plaque. Candida albicans can stick to a plaque on the denture base and engender denture stomatitis. Denture base submersion has to be carried out in traditional plant solutions to prevent denture stomatitis. Traditional plants such as black cumin and betel leaf are considered to have anti-fungal properties. This study aims to identify the comparison of antifungal properties between black cumin and betel leaf extract to Candida albicans on the acrylic resin denture base. This study is an experimental laboratory. Treatment group 1 used aquadest as a control negative, treatment group 2 used a black cumin extract with a concentration of 0.25%, while treatment group 3 used betel leaf extract with a concentrate of 50%. In every group, 9 acrylic resin pieces were soaked for 8 hours. The colony calculation was then conducted and analyzed using the Mann-Whitney test to compare the average difference level between the two tested groups. There was no significant difference level among a total colony of Candida albicans in the treatment group with a concentration of 0.25% black cumin and the treatment group with a 50% concentration of betel leaf. The result showed that the black cumin extract is no more effective in hindering the growth of Candida albicans on the acrylic resin denture base than betel leaf extract.